The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14061257
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Linear Dichroism for the Analysis of Molecular Orientation in Polymers and in Polymer Composites

Liliane Bokobza

Abstract: The mechanical properties of polymeric materials are strongly affected by molecular orientation occurring under processing conditions. Infrared dichroism is particularly well suited for characterizing polymer chain orientation at a molecular level. The usefulness of this technique has been demonstrated through various applications in homopolymers, semi-crystalline polymers, copolymers, polymer blends, as well as in polymer composites. Determination of molecular orientation can be carried out in the mid- and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 82 publications
2
13
0
Order By: Relevance
“…A similar observation was found in a previous report, where it was shown that the addition of SA reduced the thermal conductivity by approximately 30% with 1–2 wt.% of SA loading [ 22 ]. Thus, the prepared composite LDPE/LLDPE/SA (0.5–1.5 wt.%) film had a lower thermal conductivity than the neat LDPE/LLDPE blend film, and was suitable for application as a thermally insulating material.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…A similar observation was found in a previous report, where it was shown that the addition of SA reduced the thermal conductivity by approximately 30% with 1–2 wt.% of SA loading [ 22 ]. Thus, the prepared composite LDPE/LLDPE/SA (0.5–1.5 wt.%) film had a lower thermal conductivity than the neat LDPE/LLDPE blend film, and was suitable for application as a thermally insulating material.…”
Section: Resultssupporting
confidence: 91%
“…These findings can be quite convincingly explained by the various material properties that are brought about by adding SA (0.5–1.5 wt.%), either as a consequence of the process being affected by particles or as a result of the variation in SA dispersion in the extrusion blown LDPE/LLDPE blend matrix with an increase in the SA concentration. The corresponding SEM images of the samples support the XRD measurements [ 22 ].…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The ability to extract information regarding molecular orientation from p-IR data is based on the necessity that for the electric field of the incident light to excite a particular vibrational mode, a component of the electric field vector and vibrational transition dipole moment (TDM) needs to be coaligned. 52 With traditional IR instruments utilizing a globar light source, the incident light is ideally unpolarized, and hence a particular IR-active vibrational mode will absorb at least some of this light, as some component of the incident light will have an electric field aligned with the TDM. Conversely, if the incident beam is linearly polarized, maximal absorption will occur when the angle between the electric field vector and the TDM is 0, assuming the direction of travel of the incident light is orthogonal to the TDM.…”
Section: Infrared Linear Dichroism Theorymentioning
confidence: 99%